Is Germany the North Star of labor market policy? - Ulf Rinne; Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 2013)
Germany's recovery from an unemployment disease and its resilience to the Great Recession is remarkable. Its success story makes it a showcase for labor policy and labor market reforms. This paper assesses the potential of the German experience as a model for effective, evidence-based policymaking. Flexible management of working time (through overtime and short-time work, time accounts and labor hoarding), social cohesion and controlled unit labor costs, combined with a rigid, incentive-oriented labor policy supported by effective program evaluation, define the characteristics of a strong reference model. Austerity, sometimes seen as core to the German model, is not viewed as a key element.
Keywords: J68; J21; P52; O57; 330; labor market reforms; labor policy; unemployment; Great Recession; Germany; austerity